Isolation, characterization, and functional verification of salt stress response genes of NAC transcription factors in Ipomoea pes-caprae - Su, Yiren; Liu, Yang; Xiao, Shizhuo; Wang, Yuan; Deng, Yitong; Zhao, Lukuan; Wang, Yao; Zhao, Donglan; Dai, Xibin; Zhou, Zhilin; Cao, Qinghe (Frontiers in Plant Science, 2023)
Adverse environmental stress is a major environmental factor threatening food security, which is why improving plant stress resistance is essential for agricultural productivity and environmental sustainability. The NAC (NAM, ATAF, and CUC) transcription factors (TFs) play a dominant role in plant responses to abiotic and biotic stresses, but they have been poorly studied in Ipomoea pes-caprae. In this research, 12 NAC TFs, named IpNAC1–IpNAC12, were selected from transcriptome data. The homologous evolution tree divided IpNACs into four major categories, and six IpNACs were linearly associated with Arabidopsis ANAC genes. From the gene structures, protein domains, and promoter upstream regulatory elements, IpNACs were shown to contain complete NAC-specific subdomains (A–E) and cis-acting elements corresponding to different stress stimuli. We measured the expression levels of the 12 IpNACs under abiotic stress (salt, heat, and drought) and hormone treatment (abscisic acid, methyl jasmonate, and salicylic acid), and their transcription levels differed. IpNAC5/8/10/12 were located in the nucleus through subcellular localization, and the overexpressing transgenic Arabidopsis plants showed high tolerance to salt stress. The cellular Na+ homeostasis content in the mature and elongation zones of the four IpNAC transgenic sweetpotato roots showed an obvious efflux phenomenon. These conclusions demonstrate that IpNAC5/8/10/12 actively respond to abiotic stress, have significant roles in improving plant salt tolerance, and are important salt tolerance candidate genes in I. pes-caprae and sweetpotato. This study laid the foundation for further studies on the function of IpNACs in response to abiotic stress. It provides options for improving the stress resistance of sweetpotato using gene introgression from I. pes-caprae.